2011
DOI: 10.1038/oby.2010.352
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of CP‐945,598, a Selective Cannabinoid CB1 Receptor Antagonist, on Weight Loss and Maintenance

Abstract: Three double‐blind, placebo‐controlled, three‐parallel‐group, multicenter phase 3 trials were conducted to assess the efficacy and safety of CP‐945,598 for weight loss and weight‐loss maintenance. Two trials were designed to be 2 years in duration (in obese and overweight patients) and one as a 1‐year study (in obese and overweight patients with type 2 diabetes). However, the 2‐year trials and the CP‐945,598 development program were terminated before completion due to changing regulatory perspectives of CB1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The preclinical observations have been validated in humans by extensive clinical studies with rimonabant, confirming weight loss and improved lipid and glucose metabolism in treated obese humans (Van Gaal et al, 2005; Després et al, 2005; Pi-Sunyer et al, 2006). Similar findings have also been reported with taranabant and otenabant (Aronne et al, 2010; 2011). The clinical trials have, however, additionally revealed adverse psychiatric side effects, particularly depression, which has led to withdrawal of the drugs from clinical use (Beyer et al, 2010).…”
Section: Introductionsupporting
confidence: 89%
“…The preclinical observations have been validated in humans by extensive clinical studies with rimonabant, confirming weight loss and improved lipid and glucose metabolism in treated obese humans (Van Gaal et al, 2005; Després et al, 2005; Pi-Sunyer et al, 2006). Similar findings have also been reported with taranabant and otenabant (Aronne et al, 2010; 2011). The clinical trials have, however, additionally revealed adverse psychiatric side effects, particularly depression, which has led to withdrawal of the drugs from clinical use (Beyer et al, 2010).…”
Section: Introductionsupporting
confidence: 89%
“…Eighteen of the studies were randomized controlled trials of mainly dietary interventions . There were 30 randomized, placebo‐controlled trials of obesity drugs, including orlistat, cetilistat, sibutramine, topiramate, rimonabant, taranabant, CP‐945,598, and lorcaserin . All but one of the drug trials included the dietary advice of reduced energy intake in all treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…This retention programme was implemented proactively and was successful at improving upon the reported 53% 1‐year retention rate in the Rio‐North American study, which studied a similar weight loss drug in patients with similar BMI but without diabetes in the USA and Canada, also over a 1‐year time period 1, 19, and even improved upon the retention rate of Phase 3 trials conducted with more recently approved weight loss agents 2, 3, 4, 5.…”
Section: Discussionmentioning
confidence: 99%